2016
DOI: 10.1021/acs.jafc.6b03429
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Exposure to Multiple Mycotoxins from Maize-Based Complementary Foods in Tanzania

Abstract: This study estimated exposure to multiple mycotoxins in 249 infants aged between 6 and 12 months in three agro-ecological zones of Tanzania. Maize-based complementary food intakes were estimated using two 24 h dietary recalls. Using @Risk software, probabilistic exposure assessment was conducted by modeling maize intake data (kg/kg body weight/day) with previously determined multiple mycotoxin (except for ochratoxin A (OTA) and zearalenone (ZEA), present in only a few samples) contamination data (μg/kg) in mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 56 publications
(91 reference statements)
2
33
1
Order By: Relevance
“…All these studies were conducted in the general population, while others examined cancer patients’ understanding of the causes of their cancer, unveiling beliefs in curses or witchcraft [ 24 , 25 ]. In terms of cancer risk factors, studies have focused on awareness of tobacco, STDs, HIV, alcohol consumption [ 26 , 27 ], and presence of high levels of aflatoxin food contamination [ 28 30 ]. None of these studies jointly addressed awareness of multiple cancer risk factors in the population, yet this overall risk is most relevant for an all-encompassing cancer control plan.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies were conducted in the general population, while others examined cancer patients’ understanding of the causes of their cancer, unveiling beliefs in curses or witchcraft [ 24 , 25 ]. In terms of cancer risk factors, studies have focused on awareness of tobacco, STDs, HIV, alcohol consumption [ 26 , 27 ], and presence of high levels of aflatoxin food contamination [ 28 30 ]. None of these studies jointly addressed awareness of multiple cancer risk factors in the population, yet this overall risk is most relevant for an all-encompassing cancer control plan.…”
Section: Introductionmentioning
confidence: 99%
“…Contaminants such as mycotoxins, including aflatoxins and fumonisins, and heavy metals such as lead and mercury are known to be toxic, carcinogenic, and associated with child stunting (Gleason et al, ; Kumar, Mahato, Kamle, Mohanta, & Kang, ; Magoha et al, ; Wu, Narrod, Tiongco, & Liu, ). Two recent studies conducted in Ghana (Blankson & Mill‐Robertson, ) and Tanzania (Kamala et al, ) revealed an alarmingly high exposure to above‐limit aflatoxin levels in cereal‐based CFs. In this study, a comprehensive analysis of the nutritional quality and safety of locally marketed CF brands in Rwanda has been undertaken in order to provide a basis for improving nutrient intake and reducing exposure to contaminants of older infants and young children in LICs.…”
Section: Introductionmentioning
confidence: 99%
“…A study in 1989 implicated mycotoxins, specifically ZEN and its metabolites, to have an estrogenic effect, thus resulting in premature breast development and precocious sexual development in children in Puerto Rico between 1978 and 1981 [31,32]. In addition, exposure to toxigenic fungi and their metabolites have been linked to child growth and weight impairment [6,[33][34][35][36][37][38][39][40][41]. This scenario of stunting and wasting is often seen in the developing continents such as Africa [42], especially in SSA.…”
Section: Introductionmentioning
confidence: 99%